Avaliação de duas técnicas de reciclagem de pavimento flexível in situ com adição de cimento portland para a utilização em camada de base, em um trecho da rodovia Visconde de Porto Seguro/SP - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This study evaluated two cold flexible pavement recycling techniques "in situ" with the addition of Portland cement (CP II E 32) for the base layer, through analysis of the laboratory tests results and reviews of experimental sections performed on Highway Visconde Porto Seguro / SP, called SP 332, in the granting of DER-SP. Laboratory tests were conducted to prove the influence of the variability of the aggregates and the effect of Portland cement content in the dosage of recycled cold mixtures using mechanical behavior results as evaluation criteria in order to certify the technical quality of recycling layer base. The design of the passages in the experimental track allowed the determination of the flexible pavement recycling methods in situ with the mobile plant KMA 200 and the Wirtgen 2500S equipment for recycling. The monitoring the implementation, by companies, helped to understand the advantages and limitations the set of equipment employed in both recycling techniques of the experimental lane. The monitoring of experimental sections, during and after the construction process, allowed to verify that the cold recycling solution of flexible pavement for technical study, is beneficial to the structural and functional condition thereof.
Keywords: Camada de base; Pavimentos flexíveis - Reciclagem a frio; Cimento Portland - Reciclagem; Cimento Portland - Teor; Base layer; Cold recycling of flexible pavements; Recycling with Portland cement; Portland cement content; Deflections tests; ENGENHARIAS: ENGENHARIA DE MATERIAIS E METALURGICA